Inovasi Pengembangan Produk Olahan Mawar Melalui Pembuatan Teh Kuncup Mawar di KWT Nawasena, Desa Karangpring Kecamatan Sukorambi, Kabupaten Jember - Maria Azizah; Mochamat Bintoro; Leli Kurniasari; Dewi Fatmawaty Sabiku (Indonesian Journal Publisher, 2025)
Karangpring Village is located in Sukorambi District, Jember Regency, which is an area producing and supplying rose bushes in Jember Regency. The Nawasena Women Farmers Group (KWT) is one of the KWTs located in Karangpring Village, Sukorambi, Jember. This KWT manages the processing of rose products produced by farmers in Karangpring Village. The problems in developing processed products in KWT Nawasena are the lack of diversity of products produced, the quality of the products produced is still less attractive, the scale of the products is small, the limitations of processing tools and the less than optimal promotion of products through social media. This community service activity is carried out to solve partner problems, namely the development of processed rose products that are more attractive and acceptable to the market. The method of implementing the activity is divided into several stages, namely the discussion and interview stage regarding partner problems, discussion and planning to resolve partner problems, implementation of counseling, and evaluation. Based on the initial discussion and interview activities, the main problem in developing processed rose products (especially rose tea) was that product processing was carried out manually due to limited processing tools. Based on these problems, counseling was carried out on drying rose petals and buds using simple equipment with low electrical power, so that it can be applied on a household scale. In the counseling activity, counseling was also carried out on good product packaging, as well as packaging with exclusive packaging as an additional selling value of the product. The results of the questionnaire showed that 100% of the material could be accepted and understood by the participants, 90% of participants benefited from the counseling activity, and the category of participant satisfaction with the counseling activity was very good.